2021
DOI: 10.1097/mao.0000000000003313
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Toxicity of Proton Therapy for Vestibular Schwannoma: A Cohort Study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Proton radiotherapy consisted of stereotactic proton radiosurgery in 11 patients and fractionated stereotactic proton radiotherapy in 23 patients. These patients were part of a cohort that has been described before ( 15 ). We evaluated MRI and audiometry before treatment and during follow-up, specifically the first available MRI and audiometry after treatment and the most recent available MRI and audiometry after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Proton radiotherapy consisted of stereotactic proton radiosurgery in 11 patients and fractionated stereotactic proton radiotherapy in 23 patients. These patients were part of a cohort that has been described before ( 15 ). We evaluated MRI and audiometry before treatment and during follow-up, specifically the first available MRI and audiometry after treatment and the most recent available MRI and audiometry after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report on the clinical outcome and toxicity of PRT for VS in a cohort of NF2 patients to date; however, various studies have reported on PRT for sporadic VS [ 18 , 27 ]. In these studies, a combined total of 497 VS patients received passive-scatter PRT in a variety of treatment regimens between 1991 and 2018, with a prescribed dosage ranging from 12 to 60 Gy(RBE).…”
Section: Discussionmentioning
confidence: 99%
“…The local tumor control after PRT in sporadic VS ranged from 85% to 100% (median follow-up 2.2–7.4 years), which is somewhat higher than in the present NF2 patient cohort, of whom 75% did not require salvage treatment. Additionally, we found more treatment-related toxicities in our NF2 cohort than were reported in sporadic VS: hearing loss occurred in 21% to 78% of the patients, facial nerve function loss in 0% to 10% of the patients, and trigeminal neuropathy was reported in 0% to 9% of the patients after PRT in sporadic VS. One study additionally reported on vestibular symptoms and tinnitus [ 18 ]. Severe dizziness was reported in 6%, while 29% experienced mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Comparisons of hearing results between vestibular schwannoma studies or treatment groups are further hampered by differences in patient selection (eg, in pretreatment hearing levels, the average patients' age, or tumor size), different follow-up durations, and different standards for reporting on hearing (eg, the Gardner-Robertson Classification, the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS), or hearing presented as a binary outcome, as either "serviceable" or "non-serviceable," using the "50/50 rule"). [8][9][10] As a result, the reported rates of patients experiencing significant HL after vestibular schwannoma treatment range widely between 10% and 100%. 11 An additional disadvantage of using binary outcomes for hearing is that the hearing of patients with slightly better speech discrimination than 50% is classified as "serviceable," while their hearing performance is actually severely diminished.…”
mentioning
confidence: 99%